O desafio do desenvolvimento profissional docente: análise da formação continuada de um grupo de professoras das séries iniciais do ensino fundamental, tendo como objeto de discussão o processo de ensino e aprendizagem das frações - Silva, Angélica da Fontoura Garcia (2007)
This study it has as objective to analyze factors that can intervene with the professional development of teachers of the first series of Elementary School, as resulted of a formation continued with the purpose to argue questions related to the boarding of the fractionary representation of rational numbers and its different meanings. For the collection of data, (16) sessions had been carried through, of which, (3) had been destined to the application of the daily pay-test; (9) sessions had been dedicated the studies of the meanings of the fractions and to the experience of diversified methodologies; one of the sessions was dedicated to the elaboration of a work sequence, for the teachers, who were developed with its pupils in classroom. The (3) following sessions had been destined the interviews, being (2) soon after the intervention of the teachers in its classrooms and the last session, one year after the intervention, with the objective to verify the reflections made for the teachers after the research. Theoretically, we in such a way base our inquiry on theories that turn on the formation of teachers as in studies that investigate didactic questions on the mathematical object: fractionary representation of the rational number. How much to the first approach, in we support them in studies of Schön (1983), that they deal with the reflection on the practical one, extended for the quarrels of Shulman (1986), Tardif (2000), Bridge (1992) and Serrazina (1999). In relation to the didactic questions associates to the mathematical object, we use the Theory of the Conceptual Fields of Vergnaud (1990), the classification proposal for Nunes (2003) for the meanings of the fractions, the ideas of Kieren (1988) on the constructs of the rational numbers and the interpretations suggested for Ohlsson (1987). In general way, the analysis of the information gotten in allows to identify them some factors that can exert influence on the process of professional development of the teachers. One of them if relates to the relative difficulties to the mathematical knowledge of the teachers. We believe that it has necessity of a ampler approach of the concept of rational numbers, complemented for the analysis of the different meanings of its fractionary representation, as much in courses of initial formation, as continued. Another factor mentions the beliefs and conceptions to it of the teacher on the education and the learning of Mathematics, and in specific, of the mathematical object fractions. We conclude that to breach these beliefs and conceptions, is necessary a constant reflection on the practical one, over all in environments that propitiate a collaborative work. We believe that these conditions are basic for the professional development of the teachers.